2005
DOI: 10.1002/elps.200400182
|View full text |Cite
|
Sign up to set email alerts
|

Electrophoretic properties of complexes between DNA and the cationic surfactant cetyltrimethylammonium bromide

Abstract: Electrophoretic properties of complexes between DNA and the cationic surfactant cetyltrimethylammonium bromideWe use agarose gel electrophoresis to characterize how the monovalent catioinic surfactant cetyltrimethylammonium bromide (CTAB) compacts double-stranded DNA, which is detected as a reduction in electrophoretic DNA velocity. The velocity reaches a plateau at a ratio R = 1.8 of CTAB to DNA-phosphate charges, i.e., above the neutralization point, and the complexes retain a net negative charge at least up… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 36 publications
(68 reference statements)
1
22
0
Order By: Relevance
“…The decrease in fluorescence intensity at high concentrations of C 12 E 5 ( r charge >10) could be due to interactions of the fluorophore with the mixed micelles. As previously discussed, it is possible that GelStar is solubilized in the interior of the surfactant micelles, as has been observed for other nucleic acid stains [75]. In this case less fluorophore molecules would be available for DNA binding, leading to a decrease in the fluorescence intensity.…”
Section: Resultsmentioning
confidence: 84%
See 1 more Smart Citation
“…The decrease in fluorescence intensity at high concentrations of C 12 E 5 ( r charge >10) could be due to interactions of the fluorophore with the mixed micelles. As previously discussed, it is possible that GelStar is solubilized in the interior of the surfactant micelles, as has been observed for other nucleic acid stains [75]. In this case less fluorophore molecules would be available for DNA binding, leading to a decrease in the fluorescence intensity.…”
Section: Resultsmentioning
confidence: 84%
“…For a system controlled by surfactant assembly it is natural to think of a self-assembly route also for the decompaction and release of DNA from the complex. We observed that, in contrast to dendrimers, anionic and even nonionic surfactants are efficient in releasing DNA [40], [74], [75]. Figure 8A displays gel electrophoresis data where the nonionic surfactant C 12 E 5 is used to release the DNA from the CTAB/DNA complex.…”
Section: Resultsmentioning
confidence: 99%
“…Presumably the ascorbic acid will have a smaller influence and, in fact, the results obtained here are very similar to those obtained by dynamic light scattering experiments, where the experiments were conducted without the addition of fluorescence dye or antioxidants. 47 Experiments were also performed using either DAPI or GelStar as fluorescence dyes. Since the results were identical for the two dyes, we continued the experiments using GelStar only, since it gave a better contrast in these experiments and was, therefore, easier to work with.…”
Section: Resultsmentioning
confidence: 99%
“…This result may indicate that the interaction of SDS with i-PMA compact coils at low pH brings around additional compaction of the polymer. Well known is the case of DNA compaction with surfactants [38][39][40]. More importantly, this interaction probably prevents to some extent intermolecular association of the i-PMA chains themselves.…”
Section: Determining the Size Of The Particlesmentioning
confidence: 96%